Penggunaan Konjungsi Koordinatif dan Subordinatif dalam Terjemahan Surah Yusuf dan Relevansinya sebagai Bahan Ajar Bahasa Indonesia Siswa SMP Kelas IX - Arliniwaty, Junita; Arifin, Zainal (Universitas Lampung, 2024)
This research aims to describe (1) the use of conjunctions contained in the translation of Surah Yusuf and (2) its relevance as Indonesian language teaching material for grade IX junior high school students. The methodology in this research is descriptive qualitative. A qualitative descriptive approach was chosen in this research because the researcher attempted to describe the conjunctions contained in the translation of Surah Yusuf with the relevance of Indonesian language learning for class IX junior high school students. The object of this research is the coordinating and subordinating conjunctions in the translation of Surah Yusuf, while the research subject is the translation of Surah Yusuf. The data collection technique uses the note-taking technique, namely the researcher collects data by listening to and noting the translation of the Al-Qur'an which contains coordinating conjunctions and subordinating conjunctions. Data analysis uses an interactive model which includes data collection, data reduction, data presentation and conclusions. The research data source was taken from the digital translation of the Al-Qur'an in Surah Yusuf which was translated by the Ministry of Religion of the Republic of Indonesia. The research results show that (1) The coordinating conjunction has 22 data, namely: and (11 data), then (5 data), but (2 data), but (1 data), except (2 data) and namely (1 data). Meanwhile, the subordinating conjunction has 7 data, namely: because of (3 data), such as (1 data) and because of (3 data). (2) The results of this research can be used as a series of Indonesian language teaching materials in junior high schools by linking them to discussion text material. Penelitian ini bertujuan untuk mendeskripsikan (1) penggunaan konjungsi yang terkandung dalam terjemahan Surah Yusuf dan (2) relevansinya sebagai bahan ajar Bahasa Indonesia pada siswa SMP kelas IX. Metodologi dalam penelitian ini adalah deskriptif kualitatif, yaitu mendeskripsikan konjungsi yang terkandung dalam terjemahan Surah Yusuf dengan relevansi pembelajaran Bahasa Indonesia pada siswa SMP kelas IX. Objek penelitian ini adalah konjungsi koordinatif dan subordinatif pada terjemahan Surah Yusuf, sedangkan subjek penelitian adalah terjemahan Surah Yusuf. Teknik pengumpulan data menggunakan teknik simak catat, yaitu peneliti mengumpulkan data dengan menyimak dan mencatat terjemahan Al-Qur'an yang mengandung konjungsi koordinatif dan konjungsi subordinatif. Analisis data menggunakan model interaktif yang meliputi, pengumpulan data, reduksi data, sajian data, dan simpulan. Sumber data penelitian diambil dari terjemahan Al-Qur’an digital pada Surah Yusuf yang diterjemahkan oleh kementrian Agama Republik Indonesia. Hasil penelitian menunjukkan bahwa (1) konjungsi koordinatif memiliki 22 data yaitu meliputi: dan (11 data), kemudian (5 data), tetapi (2 data), namun (1 data), kecuali (2 data) dan yaitu (1 data). Sedangkan konjungsi subordinatif memiliki 7 data yaitu meliputi: karena (3 data), seperti (1 data), dan sebab (3 data). (2) Hasil penelitian ini dapat digunakan sebagai rangkaian bahan ajar Bahasa Indonesia di SMP dengan mengaitkan pada materi teks diskusi.